2019
DOI: 10.5223/pghn.2019.22.6.594
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Protein-Losing Enteropathy after Congenital Heart Disease Repair by Selective Lymphatic Embolization

Abstract: With improving survival of children with complex congenital heart disease (CCHD), postoperative complications, like protein-losing enteropathy (PLE) are increasingly encountered. A 3-year-old girl with surgically corrected CCHD (ventricular inversion/L-transposition of the great arteries, ventricular septal defect, pulmonary atresia, post-double switch procedure [Rastelli and Glenn]) developed chylothoraces. She was treated with pleurodesis, thoracic duct ligation and subsequently developed chylous ascites and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Following treatment, his serum albumin concentration improved from 1.9 g/dL to 5.0 g/dL over a period of 8 months [ 106 ]. Embolization is also commonly performed after the Fontan procedure or in patients with right heart failure and IL [ 64 , 107 , 108 ]. For more extensive disease, small numbers of reports have described positive responses to corticosteroids, octreotide, sirolimus or everolimus, propranolol [ 109 , 110 ], and tranexamic acid [ 97 , 111 ].…”
Section: Managementmentioning
confidence: 99%
“…Following treatment, his serum albumin concentration improved from 1.9 g/dL to 5.0 g/dL over a period of 8 months [ 106 ]. Embolization is also commonly performed after the Fontan procedure or in patients with right heart failure and IL [ 64 , 107 , 108 ]. For more extensive disease, small numbers of reports have described positive responses to corticosteroids, octreotide, sirolimus or everolimus, propranolol [ 109 , 110 ], and tranexamic acid [ 97 , 111 ].…”
Section: Managementmentioning
confidence: 99%
“…Lymphatic interventions for patients with lymphatic disease can also be attempted. Thoracic duct embolization and selective lymphatic embolization have been used to successfully treat patients with lymphatic insufficiency ( 75 77 ). Our institution prefers to use selective lymphatic embolization as it leaves the thoracic duct intact for other possible interventions in the future ( 64 ).…”
Section: Treatmentmentioning
confidence: 99%
“…Postoperative protein‐losing enteropathy can be treated using the dietary limitation of long‐chain triglycerides, medications including diuretics and corticosteroids, as well as surgical management, such as a Fontan fenestration 57 . More recently, it has been shown that selective glue embolization of leaking intestinal lymphatic trunks led to a prompt reversal of PLE 66 . Third, post‐Fontan patients are at a high risk of thrombus formation.…”
Section: Managementmentioning
confidence: 99%
“…B, Original Fontan procedure. C, Intra-atrial lateral tunnel Fontan technique.D, Extracardiac conduit Fontan technique with fenestrationMore recently, it has been shown that selective glue embolization of leaking intestinal lymphatic trunks led to a prompt reversal of PLE 66. Third, post-Fontan patients are at a high risk of thrombus formation.…”
mentioning
confidence: 99%